Enhancing Digital Literacy in the Elderly through Media and Technology to Prevent Hoaxes in Indonesia: A Systematic Literature Review - Yunita, Niken; Juhana, Agus; Sari, Intan Permata (Universitas Alma Ata, 2025)
The spread of hoax news among the elderly in Indonesia has been increasing due to the ease of access to information on the internet, where many elderly individuals still lack the necessary skills to filter the information they receive. Digital literacy plays a crucial role in addressing this issue, as it helps the elderly develop critical thinking skills to assess the credibility of news before sharing it. This study aims to evaluate the role of digital literacy in assisting the elderly in identifying misinformation and exploring supporting technologies in the verification process, enabling them to be more independent in filtering circulating news. This research employs the Systematic Literature Review (SLR) method to analyze various academic literature relevant to the research topic from 2014 to 2024, focusing on strategies to enhance digital literacy and the effectiveness of technology in helping the elderly recognize hoax news. The findings indicate that elderly individuals with strong digital skills are more capable of distinguishing accurate information and tend to be more cautious before sharing news with others, while technologies such as chatbots on social media can serve as effective tools for quickly and easily verifying information. Therefore, improving digital literacy through educational approaches and utilizing artificial intelligence-based technology is a crucial step in combating hoaxes in the digital era while enhancing the quality of information consumption among the elderly.